2013
DOI: 10.3390/ijms14011383
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Blood-Brain Barrier in the Formation of Brain Metastases

Abstract: The majority of brain metastases originate from lung cancer, breast cancer and malignant melanoma. In order to reach the brain, parenchyma metastatic cells have to transmigrate through the endothelial cell layer of brain capillaries, which forms the morphological basis of the blood-brain barrier (BBB). The BBB has a dual role in brain metastasis formation: it forms a tight barrier protecting the central nervous system from entering cancer cells, but it is also actively involved in protecting metastatic cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 142 publications
(115 reference statements)
2
169
0
6
Order By: Relevance
“…Most chemotherapeutic agents cannot pass through the blood-brain barrier [7,8]. Because of that, the brain is considered the first site of recurrence in an aggressive tumor such as SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Most chemotherapeutic agents cannot pass through the blood-brain barrier [7,8]. Because of that, the brain is considered the first site of recurrence in an aggressive tumor such as SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial cells of the BBB may allow brain metastases to pass through and even help facilitate this process by aiding metastatic growth. Additionally, the cancerous cells are protected from the immune system as they attempt to pass through the BBB [105].…”
Section: The Blood-brain Barrier In Cns Metastasesmentioning
confidence: 99%
“…A growing body of evidence suggests that the majority of tumor cells arrest in capillaries of a similar diameter, indicating that physical restriction initially plays the crucial role, and the stable attachments form in the following stage (27,34). Tumor cells metastasizing to the brain usually arrest via the bloodstream (31). Because of the existence of the BBB, to migrate into the brain tissue, tumor cells need markedly more time compared with other organs (31,32).…”
Section: Arrest In a New Organmentioning
confidence: 99%
“…Tumor cells metastasizing to the brain usually arrest via the bloodstream (31). Because of the existence of the BBB, to migrate into the brain tissue, tumor cells need markedly more time compared with other organs (31,32). For instance, it has been reported that ~48 h is required for lung cancer cells to extravasate into the brain, whereas extravasation into the liver takes only 6 h for the same tumor cells (33).…”
Section: Arrest In a New Organmentioning
confidence: 99%
See 1 more Smart Citation